Menganalisis Strategi-Strategi Pembelajaran Eksperimen - Mardiana, Andi; Usman, Syahruddin (Jurusan Tarbiyah STAI Al-Gazali Bone, 2025)
Experimental learning is an approach that emphasizes students' active engagement in the learning process through direct experimentation. This article aims to analyze various experimental learning strategies implemented at the secondary education level and to evaluate their effectiveness in enhancing conceptual understanding and scientific process skills. The research method employs a literature review of 15 national and international journals published between 2020 and 2024. The analysis shows that experimental learning strategies such as guided inquiry, problem-based experiments, and project-based experiments consistently improve student engagement, critical thinking skills, and knowledge retention. The discussion also addresses implementation challenges such as limited equipment, time constraints, and teacher competence. This article recommends continuous teacher training and the development of contextual experimental modules.